Empowerment of Female-Headed Households in Marginalized Communities through Islamic Legal and Sharia Economic Literacy Using an Asset-Based Community Development (ABCD) Approach - Imroatul Azizah; Moh Irfan; Amang Fathurrohman; Ida Rochmawati; M. Rikza Chamami; Syaiful Mustofa (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2026)
Background: Female-headed households in marginalized communities face complex challenges in understanding Islamic law and managing family economics, impacting household resilience and welfare. Purpose of the Study: This community service aims to enhance Islamic legal literacy and strengthen sharia-based economic capacity through local asset optimization. Methods: Using the Asset-Based Community Development (ABCD) approach, this participatory action research involved field observation, interviews, and FGDs with 30 PEKKA in Wedi Village, Bojonegoro. Results: The program successfully identified three key asset clusters: social (pengajian groups), cultural (Islamic values), and economic (culinary, sewing, farming skills). ABCD strategy activated these assets, leading to the formation of the “Srikandi Salak” business group and multidimensional transformation.